2019
DOI: 10.1111/jjns.12304
|View full text |Cite
|
Sign up to set email alerts
|

A predictive model on the hospital nurses' psychological well‐being

Abstract: Purpose The purpose of this study is to test a structural model that analyzes and comprehensively identifies the factors that affect the psychological well‐being of hospital nurses, and to reveal the direct and indirect relationships among the factors. Method The subjects of this study were 217 nurses working in four advanced general hospitals in Metropolitan City B and Province G with at least one experience of job rotation. Data were analyzed using SPSS 21.0. The characteristics of subjects and the reliabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…Psychological well-being had strong positive associations with workplace resilience ( Delgado et al, 2021 ). And studies that verified the structural model of nurses’ psychological well-being reported that social support and coping strategies have direct and indirect effects ( Arrogante et al, 2016 ; Kim & Han, 2020 ). Also, there are factors that can damage the psychological well-being of nurses such as recurrent changes in work environment ( Verhaeghe et al, 2006 ) and negative work satisfaction ( Arafa et al, 2003 ).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Psychological well-being had strong positive associations with workplace resilience ( Delgado et al, 2021 ). And studies that verified the structural model of nurses’ psychological well-being reported that social support and coping strategies have direct and indirect effects ( Arrogante et al, 2016 ; Kim & Han, 2020 ). Also, there are factors that can damage the psychological well-being of nurses such as recurrent changes in work environment ( Verhaeghe et al, 2006 ) and negative work satisfaction ( Arafa et al, 2003 ).…”
Section: Review Of Literaturementioning
confidence: 99%